'I just wanted somewhere safe': Women who are homeless with their children. (September 2015) - Kirkman, Maggie; Keys, Deborah; Bodzak, Daria; Turner, Alina
Families are the fastest growing segment of homeless populations in resource-rich countries; most are female-headed. We report on women's experiences of being homeless with their children in Victoria, Australia, emphasising their mental health. Twelve women (who between them had daily responsibility for 31 children) were interviewed, revealing complex pathways into homelessness; the two main contributors were economic decline and domestic violence, with drug use and poor mental health making lesser contributions. Homelessness appeared to have adverse effects on women's wellbeing, mental health and ontological security. There was evidence of structural barriers to good mental health being inherent in the system designed to support them, with no provision for prevention or early intervention, and limited capacity for providing residential stability. Women wanted to live somewhere that was stable, secure and safe, for themselves and their children.